Leitura e autoria em tramas audiovisuais: uma análise discursiva sobre cinemas e educações no Brasil - Pinto, Denise Machado (2024)
After ten years since the enactment of Law No. 13,006, dated June 26, 2014, which amends the current Law of Guidelines and Bases of National Education (Law No. 9,394/96) to establish that "the screening of nationally produced films shall constitute a complementary curricular component integrated into the school's pedagogical proposal, with a mandatory screening of at least two hours per month," academic discussions remain ongoing, and the implementation of the regulation is still an issue in many educational institutions. This thesis, theoretically based on Materialist Discourse Analysis, seeks to find its space for reflection, contributing to a network of research situated within the realm of cinemas and educations, in the plural, as they historicize different ways of seeing and making, traced by processes of reading and authorship production. The central question in this work is: discursively, how is it possible to understand cinema as a language technology present in Brazilian education, which, historically, mobilizes gestures of reading and authorship? To this end, the implementation of the first cultural policies aimed at the area in Brazil, dating back to the 1930s, was revisited, along with the historical movement of the creation of the National Institute of Educational Cinema (INCE). Aiming to produce a thesis archive with heterogeneous documentation, the analytical framework consists of the following materials: the 1932 Manifesto of the Pioneers of New School; the advertisement of the film Eskimo (1933) in the Revista Nacional de Educação (National Education Magazine) of 1933; Decree-Law No. 21,240, of April 4, 1932; National Cinema - A Means of Bringing Together the Country’s Inhabitants, a presidential speech from June 25, 1934; and finally, the film An Apologue by Machado de Assis (1939), from the “National Figures” series, produced by INCE. Methodologically, understanding cinema as a language technology directly impacts the construction of analytical movements based on "unveiling" designations, such as the phrase educational cinema, circulating in documents and pedagogical practices of the first half of the 20th century. The analytical path was only possible by considering the History of Discourse Analysis and the conceptual movements that structure discourse and archive reading, as they provide the theoretical support for the materials under analysis. It was concluded that the memory of what is designated as educational in cinema highlights instrumentalization as a central issue for cinema in education today. Still, the problem is even more fundamental: it lies in the tense relationships between reading and authorship established by subjects immersed in processes of meaning production in educational spaces.